2021
DOI: 10.7759/cureus.18211
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences About Device-Emitted Radiofrequency Radiation and Its Effects on Selected Brain Health Parameters in Southwest Nigeria

Abstract: IntroductionRadiofrequency radiation (RFR) is a form of non-ionising radiation that is used or emitted by a number of technologies and innovative devices including mobile phones and computers and gadgets. Exposure to RFR has been reported to have certain negative effects on human health. It is clear that quality and reliable data will be required with respect to the specific nature of RFR effects on mental health. This research considered the perceptions and exposure-related experiences of people within a Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The progress in wireless technologies has made human exposure to electromagnetic fields (EMFs) increasingly complex, so, monitoring EMF exposure levels and characterizing them are indispensable for risk communications of human exposure to EMFs [33], [34]. Various studies showed that respondents had experienced significant and negative effects of radio frequency radiation (RFR) on their mental health, indicating a critical and urgent need to educate the public on the subject [35], [36]. Data from the large-scale animal studies found animals link RFR with impacts on the heart, brain, and other organs [37].…”
Section: Introductionmentioning
confidence: 99%
“…The progress in wireless technologies has made human exposure to electromagnetic fields (EMFs) increasingly complex, so, monitoring EMF exposure levels and characterizing them are indispensable for risk communications of human exposure to EMFs [33], [34]. Various studies showed that respondents had experienced significant and negative effects of radio frequency radiation (RFR) on their mental health, indicating a critical and urgent need to educate the public on the subject [35], [36]. Data from the large-scale animal studies found animals link RFR with impacts on the heart, brain, and other organs [37].…”
Section: Introductionmentioning
confidence: 99%